PERANCANGAN MEKANISASI PANEN TANAMAN BATANG RUMPUT DENGAN PEMOTONG TIPE SIRKULAR MENGGUNAKAN PEMODELAN INVENTOR® - Ernesto Kacaribu, Brim; Safarudin, Mochamad (Technologic, 2022)
In general, traditional farmers still use the manual method which requires a large number of workers and takes longer for one hectare. With this mechanization, it is hoped that the time and cost at harvest will be faster and cheaper. It is hoped that this harvester can not only be used on one type of grass stalks plant (eg. rice) but can also be used for other types of grass stalks plants (lemongrass, sticky rice, straw). This paper produces a design using Inventor 3D to describe a mechanization system for harvesting grass stalks using a circular harvester. The crucial analysis carried out on the carrier, focuses on three things, namely the estimation of power system requirements, estimation of harvest capacity and system stability. Fits the speed-adjusting lever and the lever adjusts the height of the cutter. In its application can be used on wet land or dry land. The conclusion from the calculation is that the driving force is sufficient to move the body and cutting blades, the design capacity exceeds twice that of the manual method, and in practice the body is still stable when passing through land with an elevation of 30 degrees.